2019
DOI: 10.1007/s00404-018-5035-7
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation and qualitative evaluation of encounter decision aids in breast cancer care

Abstract: PurposeShared decision-making is currently not widely implemented in breast cancer care. Encounter decision aids support shared decision-making by helping patients and physicians compare treatment options. So far, little was known about adaptation needs for translated encounter decision aids, and encounter decision aids for breast cancer treatments were not available in Germany. This study aimed to adapt and evaluate the implementation of two encounter decision aids on breast cancer treatments in routine care.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 42 publications
1
11
0
1
Order By: Relevance
“…This is to our knowledge the first study to conduct cognitive interviews with men to adapt a prostate cancer screening decision aid after its translation. In terms of themes, our results are in line with similar studies conducted with cognitive interviews to evaluate decision aids for other preference-sensitive health decisions 36–38 43. Previous studies have shown that messages that do not clearly support cancer screening are seen as counterintuitive and that the benefits of screening are overestimated 44–46.…”
Section: Discussionsupporting
confidence: 88%
“…This is to our knowledge the first study to conduct cognitive interviews with men to adapt a prostate cancer screening decision aid after its translation. In terms of themes, our results are in line with similar studies conducted with cognitive interviews to evaluate decision aids for other preference-sensitive health decisions 36–38 43. Previous studies have shown that messages that do not clearly support cancer screening are seen as counterintuitive and that the benefits of screening are overestimated 44–46.…”
Section: Discussionsupporting
confidence: 88%
“…35 Estudos internacionais apresentam resultados semelhantes a esse estudo no que se refere à vontade dos pacientes de serem incluídos na decisão, no entanto, apresentam barreiras individuais e estruturais do sistema de saúde. [36][37][38] Implicações para a prática profissional…”
Section: Valorização Da Autonomia Dos Homens Na Tomada De Decisão Clínicaunclassified
“…To implement SDM and PDA effectively, HCP training is warranted. Studies have reported the lack of training to be contributing factors to lack of engagement of patients in SDM and proper use of PDAs [41,42]. The benefits of training are well evidenced [43,44] and it should be a pre-requisite for SDM and PDA implementation [45].…”
Section: Plos Onementioning
confidence: 99%